2021
DOI: 10.3390/cancers13225623
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recurrent Relevant Genes Reveals a Novel Role of RPL36A in Radioresistant Oral Squamous Cell Carcinoma

Abstract: Radioresistance is one of the major factors that contributes to radiotherapy failure in oral cavity squamous cell carcinoma (OSCC). By comparing the prognostic values of 20,502 genes expressed in patients in The Cancer Genome Atlas (TCGA)-OSCC cohort with (n = 162) and without radiotherapy (n = 118), herein identified 297 genes positively correlated with poor disease-free survival in OSCC patients with radiotherapy as the potential radioresistance-associated genes. Among the potential radioresistance-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…For example, nuclear factor erythroid 2-related factor 2 (Nrf2) was recently shown to be upregulated in clinically relevant radioresistant OSCC cells, and to be involved in the development of IR resistance via enhancing Nrf2-dependent glycolysis and glutathione synthesis [34]. Chen et al found that 60S ribosomal protein L36a (RPL36A) was closely related to poor prognosis in patients with OSCC treated with radiotherapy, and depletion of RPL36A sensitized OSCC cells to DNA damage and promoted G 2 /M cell cycle arrest to upregulate IR-induced apoptosis, which led to increased radiosensitivity in OSCC cells [23]. MicroRNA-125b was reported to be downregulated in OSCC cells, and exhibited an antitumor effect by reducing cell proliferation and enhancing radiosensitivity through the regulation of intercellular adhesion molecule-2 signaling [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, nuclear factor erythroid 2-related factor 2 (Nrf2) was recently shown to be upregulated in clinically relevant radioresistant OSCC cells, and to be involved in the development of IR resistance via enhancing Nrf2-dependent glycolysis and glutathione synthesis [34]. Chen et al found that 60S ribosomal protein L36a (RPL36A) was closely related to poor prognosis in patients with OSCC treated with radiotherapy, and depletion of RPL36A sensitized OSCC cells to DNA damage and promoted G 2 /M cell cycle arrest to upregulate IR-induced apoptosis, which led to increased radiosensitivity in OSCC cells [23]. MicroRNA-125b was reported to be downregulated in OSCC cells, and exhibited an antitumor effect by reducing cell proliferation and enhancing radiosensitivity through the regulation of intercellular adhesion molecule-2 signaling [36].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, resistance to radiotherapy is a primary factor for treatment failure in OSCC [23]. To better understand this observation, radioresistant OSCC cell lines CAL27R and SCC25R were established using the parental CAL27 and SCC25 cells, respectively.…”
Section: Traf4 Is Required For Maintaining Tumorigenic Properties And...mentioning
confidence: 91%
“…A study reported that the transcription of RPS27A/eS31 mRNA is increased in a p53-dependent manner, while a recent report showed that DNA double-strand breaks trigger the loss of this protein from ribosomes [ 47 , 48 ]. RPL36A/eL42 is upregulated in radioresistant tumors, while RPL37/eL37 expression increases in hypoxia and acidosis conditions [ 49 ]. All these observations suggest that the expression of RPs identified in our study is regulated and that they can contribute to ribosome heterogeneity, although we cannot rule out the possibility of an extraribosomal role.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the knockdown of ribosomal protein S27a (RPS27A) improved the therapeutic efficacy of the tyrosine kinase inhibitor imatinib in chronic myeloid leukemia [30]. Silencing of ribosomal protein large P (RPLP) promoted apoptosis and decreased radio-resistance in vitro in head and neck squamous cell cancer [31]. Furthermore, MRPL33 enhanced the sensitivity of gastric cancer cells to epirubicin, a chemotherapy drug [32].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%